CRIMINALS RELATING TO SOCIAL RELATIONS WITH PROCESSOALLY REGULATED JUSTICE LAW IN UKRAINE AND AZERBAIJAN REPUBLIC - Ахмедов, Вусал Алігісмат огли (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the article compares the composition of crimes encroaching upon social relations with the procedurally regulated administration of justice by the court, provided for by the criminal laws of Ukraine and the Azerbaijan Republic. Methods of research: comparative, the current normative legal acts are investigated. Results: the author reveals the peculiarities of the criminalization of illegal acts of this category, which are caused by the historical and political development of the societies of both countries. Discussion: the author proposes to criminalize such an act as disrespect to the court.